MALL: Global prospects and local implementation - Burston, Jack (My University, 2017)
This paper focuses on the global prospects and local implementation of Mobile-Assisted Language Learning (MALL). From a global perspective, it considers how MALL has been implemented around the world up to now and how this can be improved in the future by addressing two main challenges facing the effective integration of MALL into the foreign language curriculum: technology access and pedagogical methodology. It is shown that, owing to the ubiquitous ownership of mobile devices, it is now feasible to resolve the challenge of technology access through a Bring Your Own Device (BYOD) approach to MALL. Likewise it is shown how a constructivist, collaborative, learner-centered teaching approach can provide a solid pedagogical foundation for the effective exploitation of MALL. From the perspective of local implementations, the paper addresses the very practical question of how instructors can integrate BYOD MALL into their own curriculum.
Keywords: BYOD; Mobile devices; Implementation; Infrastructure; MALL